Participaçãp do óxido nítrico no efeito sedativo e antinociceptivo dos agonistas a2- adrenérgicos - Roman, Anna Amelia Silva Rios (2004)
The mechanism of sedative effect of clonidine (CLO), an α2-adrenoceptor agonist remain unclear. As the activation of α2-adrenoceptors induces release of nitric oxide (NO) from endothelial cells, which has led us to test the hypothesis that sedative and antinociceptive effect from systemic CLO depends on the NO-cGMP pathway mechanisms. The sleeping time in rats induced by CLO was significantly decreased by 7-NI. Thiopental sleeping time (TST) was increased by CLO, α-methyldopa, rilmenidine (RIL) and midazolam. L-NAME reduced the prolongation effect of clonidine, α-methyldopa, RIL, but did not alter the effect of midazolam on the TST. The inhibitory effect of L-NAME on CLO -dependent prolongation of TST was reversed by L-arginine. These results suggest that NO-dependent mechanisms are involved in the sedative effect of CLO. In addition, this effect seems to be specific for the sedative action of α2-adrenoceptors agonists. The possible involvement of an opioid and NO-GMPc pathway link in the antinociceptive effect of CLO was also evaluated. The antinociceptive effect induced by systemic administration of CLO and rilmenidine (RIL) was evaluated using the mice writhing tests and TFL. CLO (3 120 g/kg) and RIL induces a dose-dependent antinociceptive effect in the writhing tests and TFL. The antinociceptive effect of CLO was significantly reduced by NO-synthase and guanylyl cyclase inhibition. RIL effect was also reduced by 7-NI.The antinociceptive effect of morphine, but not CLO, was inhibited by naloxone. Our current results suggest that the antinociceptive effect of systemic clonidine does not involve the opioid receptor and is modulated by the NO-cGMP pathway.